Dedaun c.o - Wijin, Malvin; Jonas, Staenley; Mohd. Salleh, Mohd. Syueibh (2015)
Dedaun c.o is the company that focus on health product, that suitable for Malaysian peoples take it as a daily product. Moreover our product is base on tea it is very easy to carry around. The ingredients of our product is the most easiest to find because it is simple as it. The special about this product is, it base on healthy product, based on our research it can cure some sort of disease and there is some research that still in progress where our product maybe can be the solution key for cancer disease. Based on the goals above, we are venturing into healthy product industry. Annona leaves tea have the potential of being a profitable business if it is done in large scale and systematically managed. We expect that our business will become more develop in the near future because with the new innovation in our tea, the demand will increase not only during any occasion but it might be a new daily healthy product. This will give us more advantages for us to make our product more profitable and stable in the long run.